Unexpected facilitation of the pyrolysis products of potassium ferrocyanide to the electrocatalytic activity of a PdO based palladium iron composite catalyst towards ethanol oxidation reaction (EOR). (1st January 2021) - Ding, Keqiang; Qu, Runling; Han, Jingwei; Zhou, Lanjun; Zhang, Dongyue; Chen, Jiasheng; He, Xiangming; Wang, Li; Wang, Hui; Wang, Yang
Abstract: It was found, for the first time, that the pyrolysis products of potassium ferrocyanide (K4 [Fe(CN)6 ]) could significantly promote the electrocatalytic activity of the PdO based palladium iron composite catalyst towards ethanol oxidation reaction (EOR). In this work, huge carbon spheres (abbreviated as HCSs) were prepared firstly via a pyrolysis method using glucose and 1-butyl-3-methylimidazolium tetrafluoroborate as the starting materials. Secondly, PdO based palladium iron composites supported on HCSs (noted as PdO–Pd–Fe/HCSs) were successfully fabricated through a pyrolysis procedure employing PdO·H2 O, HCSs and K4 [Fe(CN)6 ] as the initial materials. When preparing PdO–Pd–Fe/HCSs, four different amounts of K4 [Fe(CN)6 ] were respectively added in the preparation system producing four kinds of samples. The sample prepared in the absence of K4 [Fe(CN)6 ] was nominated as sample b-0. And the samples prepared in the presence of 5, 10 and 20 mg K4 [Fe(CN)6 ] were, respectively, labeled as sample b-5, b-10 and b-20. It was indicated by the XRD and XPS patterns that the metallic Pd particles were the main crystalline materials of above four samples. SEM images of all synthesized samples substantially demonstrated that the added amount of K4 [Fe(CN)6 ] was a pivotal factor which could significantly affect the morphologies of the prepared samples. For sample b-0, besides some nanoparticles with a size close to 30 nm, a larger number of pores were created on the surface of the HCSs producing a honeycomb-shaped surface. Interestingly, aniseed shaped particles, cauliflower-like particles and irregular particles with a diameter more than 150 nm were, respectively, anchored on the HCSs surface of sample b-5, b-10 and b-20. Most of all, as indicated by CV and CA measurements, all the samples prepared in the presence of K4 [Fe(CN)6 ] delivered much better electrocatalytic activities towards EOR when compared to the sample prepared with no addition of K4 [Fe(CN)6 ]. For example, in the CV curves, the peak current density of the peak appearing in the positive potential scanning (peak f) for EOR on sample b-10 was nearly 6.4 times greater than that on sample b-0 (16.6 mA cm −2 vs. 2.6 mA cm −2 ). The significantly decreased charge transfer resistance and the remarkably enlarged electrochemical surface area were analyzed to be the main reasons for sample b-10 to exhibit the best electrocatalytic performance among all prepared samples. In general, a novel electrocatalyst consisting of PdO, Pd and the pyrolysis products of K4 [Fe(CN)6 ] for EOR was developed in this work, which, due to its very lower preparation cost and its satisfied electrocatalytic activity towards EOR, was very helpful to the development of Pd-based EOR electrocatalyst. Graphical abstract: Image 1 Highlights: Facilitation of the pyrolysis products to the EOR was found. Aniseed shaped metallic Pd particles were fabricated. Samples prepared with K4 [Fe(CN)6 ] showed much better EOR activity. The peak current density of EOR was significantly increased.